PENEGAKAN HUKUM PERLINDUNGAN KONSUMEN DARI PRAKTIK IKLAN YANG MENYESATKAN - Yuliska, Edwin (Fakultas Hukum Universitas Tamansiswa Padang, 2024)
Advertising is an important tool in the marketing strategy used by companies to introduce their products and services to consumers. However, misleading advertising practices are a significant problem, which can harm consumers from various aspects, including financially, health and psychologically. This writing aims to analyze existing legal protection against advertising practices that mislead consumers in Indonesia, focusing on Law Number 8 of 1999 concerning Consumer Protection and various other relevant regulations. This writing uses normative legal research methods (normative juridical) which is research that examines document studies, statutory regulations and the opinions of scholars. With discussion, namely forms of misleading advertising, the impact of misleading advertising on consumers, and legal protection for consumers. It is hoped that consumer protection from misleading advertising practices can be further improved, thereby creating a fairer and more transparent market environment.